Physics Envy: Psychologists' Perceptions of Psychology and Agreement About Core Concepts. (October 2014) - Howell, Jennifer L.; Collisson, Brian; King, Kelly M.
This study assessed the nature of psychology and its consensus regarding core content. We hypothesized that psychology possesses little agreement regarding its core content areas and thus may "envy" more canonical sciences, such as physics. Using a global sample, we compared psychologists' and physicists' perceptions regarding the nature of their field and consensus of core content areas within their respective disciplines. Results revealed that psychologists perceive their field as less theoretically and empirically grounded, and its major findings less agreed upon than physics. Psychologists also generated little consensus regarding its most important, core content areas. Discussion focuses on the importance of psychology establishing a core knowledge base and strategies to overcome "physics envy" in the classroom.